HUBUNGAN MINAT BELAJAR DENGAN HASIL BELAJAR IPA-BIOLOGI SISWA KELAS VIII SMP NEGERI 2 SIPORA KABUPATEN KEPULAUAN MENTAWAI - Ruthesarlina Saogo; Liza Yulia Sari; Ria Kasmeri (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2025)
The background of this study is the low interest in learning Science-Biology of class VIII students of SMP Negeri 2 Sipora, which has an impact on student learning outcomes. It can be seen that during the learning process, students are less serious, often ask permission to go in and out of class, pay less attention to the material presented, prefer to chat with their deskmates, are reluctant to ask when the material is not understood, and are lazy to do assignments. Students also appear passive during group discussions. This problem is largely caused by students' lack of self-confidence, which affects their active involvement in learning and has an impact on their learning outcomes. The learning outcomes of Science-Biology of class VIII students of SMP Negeri 2 Sipora are still relatively low, as seen from the percentage of learning outcomes that are still below the KKM 75 in the Odd Semester Mid-Semester Exam for the 2023/2024 Academic Year. This study aims to determine the relationship between learning interest and students' Science-Biology learning outcomes. The research method used is descriptive research with a total sampling technique. The research sample consisted of 131 class VIII students of SMP Negeri 2 Sipora. The research instrument was a questionnaire of learning interest, and data analysis techniques included correlation analysis, coefficient of determination, and simple linear regression. The results of the data analysis showed that there was a significant relationship between learning interest and the learning outcomes of Science-Biology of class VIII students of SMP Negeri 2 Sipora during the Science-Biology learning process.